Regulation of mitochondrial morphology and cristae architecture by the TLR4 pathway in human skeletal muscle - Castro-Sepulveda, Mauricio; Tuñón-Suárez, Mauro; Rosales-Soto, Giovanni; Vargas-Foitzick, Ronald; Deldicque, Louise; Zbinden-Foncea, Hermann (Frontiers in Cell and Developmental Biology, 2023)
In skeletal muscle (SkM), a reduced mitochondrial elongate phenotype is associated with several metabolic disorders like type 2 diabetes mellitus (T2DM). However, the mechanisms contributing to this reduction in mitochondrial elongate phenotype in SkM have not been fully elucidated. It has recently been shown in a SkM cell line that toll-like receptor 4 (TLR4) contributes to the regulation of mitochondrial morphology. However, this has not been investigated in human SkM. Here we found that in human SkM biopsies, TLR4 protein correlated negatively with Opa1 (promitochondrial fusion protein). Moreover, the incubation of human myotubes with LPS reduced mitochondrial size and elongation and induced abnormal mitochondrial cristae, which was prevented with the co-incubation of LPS with TAK 242 . Finally, T2DM myotubes were found to have reduced mitochondrial elongation and mitochondrial cristae density. Mitochondrial morphology, membrane structure, and insulin-stimulated glucose uptake were restored to healthy levels in T2DM myotubes treated with TAK 242 . In conclusion, mitochondrial morphology and mitochondrial cristae seem to be regulated by the TLR4 pathway in human SkM. Those mitochondrial alterations might potentially contribute to insulin resistance in the SkM of patients with T2DM.